Effectiveness of a fundamental motor skill intervention for 4-year-old children with autism spectrum disorder: A pilot study. (November 2015) - Bremer, Emily; Balogh, Robert; Lloyd, Meghann
A wait-list control experimental design was employed to investigate the effectiveness of a fundamental motor skill intervention at improving the motor skills, adaptive behavior, and social skills of 4-year-old children with autism spectrum disorder (experimental n = 5, control n = 4); the impact of intervention intensity was also explored. The experimental group significantly improved their object manipulation and overall motor scores from pre- to post-intervention. The wait-list control design revealed no group-by-time interactions; however, with the groups combined time was a significant factor for all motor variables. There were no significant changes in adaptive behavior and social skills. These preliminary findings suggest that a fundamental motor skill intervention may benefit young children with autism spectrum disorder. Future research with larger samples is warranted.